Differential in Utilization of Forest Products among the Users of Community Forest in Kaski District (Prithvi Academic Journal, 2022)
There is a different level of preference on the forest products such as timber, fuel wood, tree fodder/grass, non-timber forest products and leaf litter. Different people have different usage of forest products. In this context, this study has tried to analyze the differential in utilization of forest products among the users of community forest. For this purpose, the data were collected from 165 households out of 280 users' of Dangsimaryan community forest of Kaski district, using the structured questionnaire following the interview techniques. The multistage sampling technique was used to select the samples for the data collection. The data were collected from the members of the community forest. Pre-test was carried out before finalizing the questionnaire. A verbal informed consent was obtained from each participant. The Kruskal Wallis test was used to test the difference on the utilization of forest products among the respondents from different economic backgrounds. People prefer timber and fuelwood more than other forest products, so tree species is more meaningful to them. It is found that there is a significant difference on the preference of fuel wood, tree fodder/ grass and leaf litter among different economic classes of the respondents.